An innovative development of a whole-body diagnostic device led to the ingenious discovery of comprehensive digital medicine that has potential to lead to health promotion of humankind and consequential rapid economic growth of the world - Biswas, Abhijit; Ramasubramanian, Krishnan (International Journal of Advances in Medicine, 2024)
After working for a few decades, gas-discharge-visualization (GDV) device, alternatively called electro-photonic-imaging (EPI) device, was innovatively developed by Prof. K.G. Korotkov in 1995. The sophisticated GDV diagnostic device additionally is being used as an important tool for generating comprehensive-digital-medicine by feeding an electromagnetic signal from the GDV device to the comprehensive-digital-medicine preparation device, involving very low cost. This medicine helps to achieve near zero disease-levels in the various organs as well as the immune, endocrine and nervous systems of all health-conscious persons, who want to continue sincerely with the optimal combination of the preventive medicines of digital-homeopathy and evolved-homeopathy, and occasional GDV (once in a month) check-up. When this condition is achieved, about 20 years age-reduction is felt along with improvement of physical and mental stamina and increment in longevity. To begin with, the global organizations and insurance companies will have to provide for the first few years fund and offer suitable incentives (may be, appropriate annual cash-incentives after remaining under coverage of comprehensive-digital-medicine prevention scheme), since vast majority of the apparently healthy part of humankind believe that they’re healthy, although all of their organs are having imperceptible disease level between 0.8 to 1.0, and such disease level in immune system (including Spleen) cannot prevent tumors/ cancer and many other severe diseases. After a span of few years, global GDP can increase by 5% over a year (in contrast with the present 3%), when this increased GDP (due to better health and increase in retirement age) can fund such schemes.